(untitled) (Praxis Educativa, 2025)
The ways of playing are not neutral; they shape subjectivities and modes of relating. Play and playing participate in power struggles. While some types of play align with hegemonic interests due to their structure, cooperative play offers an alternative framework based on participation and horizontal collaboration in solving common challenges. Therefore, this type of play constitutes an exercise in direct democracy that promises a new horizon for the era. However, given its marginalized status compared to other forms of play, it is necessary to create spaces for practicing this type of play, which in turn allows for investigating its social and political implications.